ETIKA LINGKUNGAN SISWA SEKOLAH DASAR DI PEKANBARU - Nur Salwa; Eddy Noviana (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2019)
Humans have an important role in protecting nature or the environment; therefore, environmental ethics are needed to preserve the environment. The Adiwiyata program can instill environmental ethics in school communities, especially students. This research was conducted to describe environmental ethics as reflected in the behavior of elementary school students around the school canteen. The indicators of environmental ethics observed around the canteen included: (1) responsibility for the environment, (2) solidarity with the environment, (3) compassion and care for nature or the environment, (4) not damaging nature or the environment, and (5) living simply and in harmony with nature. This type of research was descriptive research, and the research instruments were observation and interviews. The results showed that environmental ethics had not yet been reflected in students’ behavior. Student awareness in protecting the environment was still low, as seen from the lack of environmental ethics in their behavior. Schools should pay more attention to environmental ethics in students’ behavior and implement activities that can instill or enhance environmental ethics among students.